Long-term Effect of Fine Particulate Matter on Hospitalization with Dementia - Lee, Mihye (Environ Pollut, 2019)
BACKGROUND: New evidence suggests that PM(2.5) is associated with dementia (LOD). However, epidemiological studies for the entire population have not been implemented yet. METHODS: We utilized approximately 94 million follow-up records from fee-for-service Medicare records for 13 million Medicare beneficiaries residing in the southeastern U.S. from 2000 to 2013. For exposure to PM(2.5), we used spatially and temporally continuous data that improved those from monitors. To account for time-varying PM(2.5) levels, the Cox model with the Andersen-Gill counting process was applied. Stratified analyses by subtype of dementia and levels of urbanization of residence were performed. RESULTS: During a median follow-up of 6 years, 1,409,599 hospitalizations for dementia occurred. The adjusted hazard ratio (HR) of hospitalization with dementia was 1.049 (95% confidence interval [CI], 1.048 to 1.051) per 1 μg/m(3) increase in annual PM(2.5). In particular, the hazard ratio for vascular dementia (HR, 1.086; 95% CI, 1.082 to 1.090) was high. The magnitude of the effect grew as the level of urbanization increased (HR, 1.036; 95% CI, 1.031 to 1.041 in rural areas versus HR, 1.052; 95% CI, 1.050 to 1.054 in metropolitan areas). CONCLUSIONS: Long-term exposure to higher PM(2.5) was associated with increased hospitalizations with dementia.